Thermal shock response via weakly coupled peridynamic thermo-mechanics. (15th December 2017) - D'Antuono, Pietro; Morandini, Marco
Abstract: A 3D peridynamic formulation of the thermo-mechanical problem allows to efficiently simulate the occurrence and propagation of cracks due to extreme thermal loading. The model is weakly coupled since no internal heat generation due to material deformation and damage is accounted for. As such, it is suitable to simulate low strain rate phenomena. Since the typical time scales of the mechanical and thermal systems may differ of several orders of magnitude, using a multirate explicit integration technique is suggested by the nature of the problem itself. Finally, the proposed formulation is used to model the thermal shock behavior of thin and thick slabs, in order to observe respectively a 2D ordered set of parallel cracks and a 3D honeycomb crack pattern addressed as columnar jointing.